Response to Interferon-Free Direct Antivirals (DAAS) Treatment in HCV-Related Subcutaneous Lipoma-Like Marginal Zone B-Cell Lymphoma - Maria Lucia De Luca; Laura Lombardi; Germana Tartaglia; Francesca Fazio; Alessio Di Prima; Laura Cesini; Alessandra Serrao; Martina Canichella; Alessandro Pulsoni (Mediterranean Journal of Hematology and Infectious Diseases, 2019)
In 2010 a new entity termed “lipoma-like” HCV related marginal zone B-NHL was described. The etiological link between HCV infection and B-NHL has been extensively investigated in several epidemiological, biological and therapeutic studies and large experiences in literature demonstrated indolent lymphoma’s regression after antiviral therapy. HCV-related indolent NHL response to interferon-ribavirin-based antiviral therapy is well documented, while evidence of the efficacy of interferon-free direct-acting antivirals (DAAs) in this subset of lymphoma is also currently increasing. In this article we report two cases of HCV-related subcutaneous “lipoma-like” Marginal Zone B-cell lymphoma, treated with DAAs. Sustained virological response (SVR) with reduction of MZL localizations, persisting to date, were obtained in both patients. These data originally demonstrate the efficacy of DAAs in this rare entity.